Lamotrigine loaded PLGA nanoparticles intended for direct nose to brain delivery in epilepsy: pharmacokinetic, pharmacodynamic and scintigraphy study. Issue 1 (1st January 2021) - Shah, Pranav; Dubey, Priya; Vyas, Bhavin; Kaul, Ankur; Mishra, Anil Kumar; Chopra, Dimple; Patel, Priya
Abstract: The present study aimed to investigate the brain targeting efficacy of Lamotrigine (LTG) loaded PLGA nanoparticles (LTG-PNPs) upon intranasal administration. LTG-PNPs were fabricated through the emulsification-solvent evaporation technique and evaluated for % Entrapment efficiency, particle size, in-vitro release, surface morphology, crystallinity, ex-vivo permeation & thermal behaviour. Biodistribution, gamma scintigraphy, and pharmacodynamic studies were performed in BALB/c mice, New Zealand rabbits, and Wistar rats respectively. LTG-PNPs exhibited % EE 71%; particle size 170.0 nm; Polydispersity index 0.191; zeta potential −16.60 mV. LTG-PNPs exhibited a biphasic release pattern. Biodistribution and gamma scintigraphy studies proved a greater amount of LTG in the brain following intranasal delivery of LTG-PNPs in comparison to LTG-SOL. Pharmacodynamic studies demonstrated delayed seizure onset time with LTG-PNPs in comparison to LTG-SOL. Intranasal administration of LTG-PNPs provided prolonged release, higher bioavailability, and better brain targeting bypassing the BBB. The developed formulation could be administered as a once-a-day formulation that would reduce the dosing frequency; dose; dose-related side effects; cost of the therapy and would be beneficial in the management of epilepsy as compared to the LTG-SOL. However, the proof of concept generated through these studies needs to be further validated in higher animals and human volunteers. Graphical Abstract: UF0001